INFLUENCE OF BASE SUBSTANTIAL DIFFERENTIAL SETTLEMENTS ON STRUCTURAL SYSTEMS SEISMIC STABILITY LEVEL - Khokhlin, Denуs (Proceedings of National Aviation University (archive), 2016)
Introduction: Urgent question of base substantial differential settlements influence by different origin on building structural systems seismic stability is considered in the article. The aim of research is estimate of such influence degree. Selection of analysis method: It had been suggested to use of nonlinear static analysis by the spectrum capacity method for analysis and then this method was used. Numerical estimate of base substantial differential settlements influence on structural system seismic stability: Numerical experiment which shows degree of seismic stability reduction depending of base differential settlements level is introduced. The experiment was made on the ground of wall system model of complex masonry and also reinforced concrete constructions. Nonlinear analysis was done on the consecutive influence of base differential slumping deformations and horizontal seismic loads. Consideration of the analysis results and conclusions: Consequently it was revealed, that force influence of base substantial differential settlements is able to significant reduce seismic stability of construction systems (from 1 intensity degree down to practically completely loss of seismic stability). This fact determines necessity of accounting of base substantial differential settlements and seismic force influence combination when there is capability of occurrence both of them. In this case, it is necessary to take into account sequential influence of the loads and also recommended using of nonlinear analysis by the principles of the capacity spectrum method. It is also necessary to specify level of inelastic deformations and damages evolution by experimentally confirmed values.